Implications of Circular Economy, Supply Chain Management Innovation and Sustainability on Organisational Performance - Gregorius Paulus Tahu; Anik Yuesti; Daniel Manek; Yenny Verawati (International Journal of Supply Chain Management, 2020)
Abstract-This study analysed the effects of circular economy, supply chain management innovation and sustainability on organisation performance. A total of 163 respondents, who are public sector employees in Bandung City, participated in this study. The hypotheses were tested using the descriptive and verification research methods. Data were collected using a questionnaire, and structural equation modelling analysis through the LISREL programme was employed. Results indicated that circular economy and supply chain management innovation significantly and positively influence organisation performance. Similarly, supply chain management innovation significantly and positively influences sustainability, which also significantly and positively influences organisation performance.